Nonlinear structural dynamics using FE methods - Doyle, James F., 1951- (Cambridge : Cambridge University Press, 2015)
Nonlinear Structural Dynamics Using FE Methods emphasises fundamental mechanics principles and outlines a modern approach to understanding structural dynamics. This will be useful to practising engineers but also students who will find advanced topics presented in an accessible manner. The book successfully presents the fundamentals of structural dynamics and infuses them with finite element (FE) methods. First, the author establishes and develops mechanics principles that are basic enough to form the foundations of FE methods. Second, the book presents specific computer procedures to implement FE methods so that general problems can be 'solved' - that is, responses can be produced given the loads, initial conditions and so on. Finally, the book introduces methods of analyses to leverage and expand the FE solutions.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Structural analysis (Engineering) -- Mathematics; Finite element method; Nonlinear theories